2022
DOI: 10.3390/ijms23020906
|View full text |Cite
|
Sign up to set email alerts
|

Novel Putative Transposable Element Associated with the Subtype E5 Botulinum Toxin Gene Cluster of Neurotoxigenic Clostridium butyricum Type E Strains from China

Abstract: Previously, a whole-genome comparison of three Clostridium butyricum type E strains from Italy and the United States with different C. botulinum type E strains indicated that the bont/e gene might be transferred between the two clostridia species through transposition. However, transposable elements (TEs) have never been identified close to the bont/e gene. Herein, we report the whole genome sequences for four neurotoxigenic C. butyricum type E strains that originated in China. An analysis of the obtained geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Since we have not yet resolved the evolutionary forces driving BoNT uptake, maintenance, and diversity in clostridia and related organisms, we may under-appreciate the diversity and functional distinctions of the many members of the BoNT family of protein toxins concerning human pathology and pharmacology. One study in this Special Issue that addresses the horizontal transfer of bont genes in clostridia describes the identification of transposable elements associated with BoNT/E5 in C. butyricum [19]. Previous studies have indicated the potential horizontal transfer of bont genes by plasmid conjugation combined with potential chromosomal plasmid integration events and proposed the descent of bont genes from a precursor protein family with adaptation towards developing into toxins producing vertebrate paralysis followed by diversification [1,20,21].…”
mentioning
confidence: 99%
“…Since we have not yet resolved the evolutionary forces driving BoNT uptake, maintenance, and diversity in clostridia and related organisms, we may under-appreciate the diversity and functional distinctions of the many members of the BoNT family of protein toxins concerning human pathology and pharmacology. One study in this Special Issue that addresses the horizontal transfer of bont genes in clostridia describes the identification of transposable elements associated with BoNT/E5 in C. butyricum [19]. Previous studies have indicated the potential horizontal transfer of bont genes by plasmid conjugation combined with potential chromosomal plasmid integration events and proposed the descent of bont genes from a precursor protein family with adaptation towards developing into toxins producing vertebrate paralysis followed by diversification [1,20,21].…”
mentioning
confidence: 99%